2010
DOI: 10.1111/j.1365-2958.2010.07498.x
|View full text |Cite
|
Sign up to set email alerts
|

Discretely calibrated regulatory loops controlled by ppGpp partition gene induction across the ‘feast to famine’ gradient in Escherichia coli

Abstract: SummaryBacteria comprehensively reorganize their global gene expression when faced with starvation. The alarmone ppGpp facilitates this massive response by co-ordinating the downregulation of genes of the translation apparatus, and the induction of biosynthetic genes and the general stress response. Such a large reorientation requires the activities of multiple regulators, yet the regulatory network downstream of ppGpp remains poorly defined. Transcription profiling during isoleucine depletion, which leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(134 citation statements)
references
References 49 publications
4
129
1
Order By: Relevance
“…Many genes involved in stress responses confer strong fitness benefits in vivo, suggesting that the bee gut is a challenging environment in which S. alvi is exposed to toxins, low nutrient availability, and fluctuating O 2 , pH, and temperature. Among genes required in vivo were those underlying the ppGpp stringent response and Lrp, a master regulator that is induced by ppGpp upon amino acid starvation in other bacteria (29). In turn, Lrp can modulate expression of various amino acid synthesis enzymes and transporters to ensure cell survival (30).…”
Section: Significancementioning
confidence: 99%
“…Many genes involved in stress responses confer strong fitness benefits in vivo, suggesting that the bee gut is a challenging environment in which S. alvi is exposed to toxins, low nutrient availability, and fluctuating O 2 , pH, and temperature. Among genes required in vivo were those underlying the ppGpp stringent response and Lrp, a master regulator that is induced by ppGpp upon amino acid starvation in other bacteria (29). In turn, Lrp can modulate expression of various amino acid synthesis enzymes and transporters to ensure cell survival (30).…”
Section: Significancementioning
confidence: 99%
“…74-77 This initial response is followed by down-regulation of many growth-related genes and up-regulation of the general stress response genes by σ S -bound RNA polymerase. 18,19 …”
Section: Why Degrade Trna?mentioning
confidence: 99%
“…Repression or activation of target genes is dependent on discriminator sequences encoded in the promoter region (12). Furthermore, (p)ppGpp promotes alternative factor usage (64). In Firmicutes, (p)ppGpp is unable to bind to RNAP (8,9).…”
Section: Figmentioning
confidence: 99%
“…This is not to say that the contributions of subtle fluctuations in (p)ppGpp pools to the control of core cellular processes and growth rate have been completely overlooked (59)(60)(61)(62). However, more recently, the notion that (p)ppGpp exerts important regulatory effects at concentrations below those needed to activate the SR has been more thoroughly revisited (10,54,63,64). In an elegant study using cells that were progressively starved, the Conway lab identified two distinct regulatory cascades activated by (p)ppGpp in E. coli (64).…”
Section: (P)ppgpp Beyond the Sr: Basal (P)ppgpp Pools And Cell Homeosmentioning
confidence: 99%
See 1 more Smart Citation